Beyond nutritional immunity: immune-stressing challenges basic paradigms of immunometabolism and immunology - LeGrand, Edmund K. (Frontiers in Nutrition, 2025)
Pathogens have the well-known advantage of rapid evolution due to short generation times and large populations. However, pathogens have the rarely noted disadvantage of the vulnerability to stress involved in proliferation as well as being localized. Presented here are numerous new paradigms in immunology, and especially immunometabolism, which are derived from examining how hosts capitalize on pathogen vulnerabilities to stress. Universally, proliferation requires both resources and synthesis, which are vulnerable to resource-limiting stress and damaging/noxious stress, respectively. Pathogens are particularly vulnerable to stress at the time when they are most threatening—when they are proliferating. Since immune cells actively controlling pathogens (effector cells) typically do not proliferate at infected sites, there is a “stress vulnerability gap” wherein proliferating pathogens are more vulnerable to any type of stress than are the attacking effector cells. Hosts actively stress vulnerable proliferating pathogens by restricting resources (resource-limiting stress) and generating noxious waste products (damaging/disruptive stress) in a fundamental defense here-in termed “immune-stressing.” While nutritional immunity emphasizes denying pathogens micronutrients, immune-stressing extends the concept to restricting all resources, especially glucose and oxygen, coupled with the generation of noxious metabolic products such as lactic acid, reactive oxygen species (ROS), and heat to further harm or stress the pathogens. At present much of the field of immunometabolism centers on how nutrition and metabolism regulate immune function, a central feature being the inefficient use of glucose via aerobic glycolysis (with much lactate/lactic acid production) by effector immune cells. In contrast, immune-stressing emphasizes how the immune system uses nutrition and metabolism to control infections. Immune-stressing addresses effector cell glycolysis at the infected site by noting that the high uptake of glucose linked with high output of lactic acid is an ideal double-pronged stressor targeting proliferating pathogens. Once the basic vulnerability of pathogen proliferation is recognized, numerous other paradigms of immunometabolism, and immunology as a whole, are challenged.